Dendritic cells exposed to triiodothyronine deliver pro-inflammatory signals and amplify IL-17-driven immune responses - Alamino, Vanina Alejandra (2019)
Although a cross-talk between immune and endocrine systems has been well established, the precise pathways by which these signals co-regulate pro- and antiinflammatory responses on antigen-presenting cells remain poorly understood. In this work we investigated the mechanisms by which triiodothyronine (T3) controls T cell activity via dendritic cell (DC) modulation. Methods: DCs from wild-type (WT) and IL-6-deficient mice were pulsed with T3. Cytokine production and programmed death protein ligands (PD-L) 1 and 2 expression were assayed by flow cytometry and ELISA. Interferon-regulatory factor-4 (IRF4) expression was evaluated by RT-qPCR and flow cytometry. The ability of DCs to stimulate allogenic splenocytes was assessed in a mixed lymphocyte reaction and the different profile markers were analyzed by flow cytometry and ELISA. For in vivo experiments, DCs treated with ovalbumin and T3 were injected into OTII mice. Proliferation, cytokine production, frequency of FoxP3+ regulatory T (Treg) cells and PD-1+ cells were determined by MTT assay, ELISA and flow cytometry, respectively. Results: T3 endows DCs with pro-inflammatory potential capable of generating IL-17-dominant responses and down-modulating expression of PD-L1 and 2. T3-stimulated WT-DCs increased the proportion of IL-17-producing splenocytes, an effect which was eliminated when splenocytes were incubated with T3-treated DCs derived from IL-6-deficient mice. Enhanced IL-17 expression was recorded in both, CD4- and CD4+ populations and involved the IRF-4 pathway. Particularly, gd-T cells but not natural killer (NK),NKT, B lymphocytes nor CD8+ T cells were the major source of IL-17-production from CD4- cells. Moreover, T3-conditioned DCs promoted a decrease of the FoxP3+ Treg population. Furthermore, T3 down-modulated PD-1 expression on CD4- cells thereby limiting inhibitory signals driven by this co-inhibitory pathway. Thus, T3 acts at the DC level to drive proinflammatory responses in vitro. Accordingly, we found that T3 induces IL-17 and IFNg-dominant antigen-specific responses in vivo. Conclusion: These results emphasize the relevance of T3 as an additional immune-endocrine checkpoint and a novel therapeutic target to modulate IL-17-mediated pro-inflammatory responses.